Effective fluid replacement - Horswill, C. A. (International Journal of Sport Nutrition and Exercise Metabolism, 1998)
As a result of exercise-induced sweating, athletes and trained individuals can lose up to 3 L of fluid per hour. Fluid replacement is required to maintain hydration and allow the athlete to continue to perform. Inadequate fluid intake will adversely affect temperature regulation, cardiovascular function, and muscle metabolism. To maximize fluid intake and effectively replace fluid, athletes must employ behavioral strategies. Athletes can also select beverages with characteristics that complement their behavioral efforts. Palatability, rapid absorption, retention of the fluid, and ergogenicity are the major attributes to consider for enhancing hydration during training and physical activity. Int J Sport Nutr 1998 Jun;8(2):175-95